Introduction to Positioning Algorithms - Pahlavan, Kaveh (Indoor Geolocation Science and Technology, 2019)
In cooperative localization, geometric equations related to location of multiple target tags (TG) are used as a part of positioning algorithm. This chapter begins with describing basic triangulation methods for positioning a TG with minimum reference points using different combinations of measurements of distance and angle of arrival. Recursive least square (RLS) algorithm is very useful in navigation of mobile TGs. The RLS algorithm is also applicable to any other geometric localization algorithm for continual positioning using updated measurements from a mobile using distance or angle of arrival. Distance-based positioning is the choice of all popular time of arrival -based positioning systems. In outdoor urban areas, when the line-of-sight (LOS) path between the transmitter and the receiver is blocked by a building, we have an obstructed-LOS condition with a blocked direct path. Numerical solution to the localization problem offers itself as an alternative with more robust positioning of a location.